Mathematics: a vital tool in everyday life - Jean-Pierre, Herlins Coeurly; Jean-Pierre, Webster Jimmy (Revista Científica Foz, 2026)
This article explores the role of mathematics, often perceived as abstract, in everyday life. It highlights practical applications such as personal finance, cooking, healthcare, and technology, showing that basic math skills are crucial for informed decision-making. Drawing on authors like Boero, Duval, and Gerdes, it argues that more contextualized and accessible teaching methods can overcome negative perceptions. Mathematics is presented as a powerful tool to develop critical thinking, solve problems, and better understand the world.